2009
DOI: 10.1002/jcb.22238
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of synovial CD‐105+ human mesenchymal stem cells into chondrocyte‐like cells through spheroid formation

Abstract: Mesenchymal stem cells (MSCs) have the capacity to differentiate into several cell lineages, some of which can generate bone, cartilage, or adipose tissue. The presence of MSCs in the synovial membrane was recently reported. Data from comparative studies of MSCs derived from various mesenchymal tissues suggest that MSCs from synovial membranes have a superior chondrogenesis capacity. Previous chondrogenic differentiation studies have used the total population of MSCs, including cells with several MSC markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 40 publications
3
78
0
4
Order By: Relevance
“…Classically hMSCs were isolated and expanded as adherent monolayer cultures, but it was soon recognized that centrifugation of the cells to form micropellets or large aggregates greatly enhanced their chondrogenic differentiation that slowly occurred over several weeks (18,27). However, several recent publications demonstrated that culture of MSCs in 3D or as spheroids for shorter periods of time improved their therapeutic potential by increased expression of genes such as CXCR4 to promote adhesion to endothelial cells or of IL-24 that has tumor suppressing properties (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically hMSCs were isolated and expanded as adherent monolayer cultures, but it was soon recognized that centrifugation of the cells to form micropellets or large aggregates greatly enhanced their chondrogenic differentiation that slowly occurred over several weeks (18,27). However, several recent publications demonstrated that culture of MSCs in 3D or as spheroids for shorter periods of time improved their therapeutic potential by increased expression of genes such as CXCR4 to promote adhesion to endothelial cells or of IL-24 that has tumor suppressing properties (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been a series of publications on aggregation of MSCs either as a procedure for enhancing chrondrogenic differentiation of the cells (17)(18)(19) or to increase their therapeutic potential (20)(21)(22)(23). Because aggregated hMSCs were detected in the pulmonary microemboli observed after i.v.…”
mentioning
confidence: 99%
“…Isolation is traditionally based on the typical capacity of MSCs to adhere to plastic surfaces. [18][19][20] One disadvantage of isolating cells by adherence, however, is the nonspecificity of this approach despite the use of selected sera and media for culture initiation. This is due to the fact that MSCs represent only a very rare fraction of the starting cell population that contains other, more abundant cells types, several of which also adhere to standard cell culture surfaces.…”
Section: Conventional Approaches To Human Msc Isolation: Adherencementioning
confidence: 99%
“…Data gained from 3D in vitro methods may help to bridge the gap between traditional 2D culture studies and in vivo pre-clinical animal models (Rangarajan et al, 2004;Griffi th and Swartz, 2006;Yamada and Cukierman, 2007;Pampaloni et al, 2007;Hutmacher, 2010). Signifi cant alterations in cell behaviour have been identifi ed, when they are grown in 3D compared to 2D conditions; including changes in cell morphology (Cukierman et al, 2001), differentiation capacity (Arufe et al, 2009;Wang et al, 2009b), replicative ability (Grayson et al, 2006), cell signalling (Cukierman et al, 2002;Green and Yamada, 2007) as well as signifi cant increases in their therapeutic potential (Tapp et al, 2008;Wang et al, 2009a;Dittmer et al, 2009;Bartosh et al, 2010;Frith et al, 2010). For example, we have previously shown that MSCs grown in dynamic 3D culture conditions can promote osteogenic and adipogenic differentiation potential (Frith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%